Low-Dose Radiation Can Cause Epigenetic Alterations Associated With Impairments in Both Male and Female Reproductive Cells - Leung, Chi Tim; Yang, Yi; Yu, Kwan Ngok; Tam, Nathan; Chan, Ting Fung; Lin, Xiao; Kong, Richard Yuen Chong; Chiu, Jill Man Ying; Wong, Alice Sze Tsai; Lui, Wing Yee; Yuen, Karen Wing Yee; Lai, Keng Po; et al. (Frontiers in Genetics, 2021)
Humans are regularly and continuously exposed to ionizing radiation from both natural and artificial sources. Cumulating evidence show adverse effects of ionizing radiation on both male and female reproductive systems, including reduction of testis weight and sperm count, and reduction of female germ cells and premature ovarian failure. While most of the observed effects were caused by DNA damage and disturbance of DNA repairment, ionizing radiation may also alter DNA methylation, histone and chromatin modification, leading to epigenetic changes and transgenerational effects. However, the molecular mechanisms underlying the epigenetic changes and transgenerational reproductive impairment induced by low-dose radiation remain largely unknown. In this study, two different types of human ovarian cells and two different types of testicular cells were exposed to low-dose of ionizing radiation, followed by bioinformatics analysis (including gene ontology functional analysis and Ingenuity Pathway Analysis), to unravel and compare epigenetic effects and pathways changes in male and female reproductive cells induced by ionizing radiation. Our findings showed that the radiation could alter the expression of gene cluster related to DNA damage responses through the control of MYC. Furthermore, ionizing radiation could lead to gender-specific reproductive impairment through deregulation of different gene networks. More importantly, the observed epigenetic modifications induced by ionizing radiation are mediated through the alteration of chromatin remodeling and telomere function. This study, for the first time, demonstrated that ionizing radiation may alter the epigenome of gem cells, leading to transgenerational reproductive impairments, and correspondingly call for research in this new emerging area which remains almost unknown.